2016
DOI: 10.22146/agroekonomi.17381
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Impor Gandum Indonesia

Abstract: The purpose of this research are to determine the factors that influence the Indonesian wheat imports and the trend of Indonesian wheat imports. The Keywords: wheat, import, Indonesia INTISARITujuan dari penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi impor gandum Indonesia dan untuk mengetahui trend impor gandum Indonesia. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif dengan menggunakan data time series dari tahun 1992-2011. Variabel-variabel yang digun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…From 1996 to 1999, it had declined to 15.4 grams capita -1 day -1 , but increased again from 1999 to 2002 to 21.7 grams capita -1 day -1 and continued to increase until 2005 to 27.3 grams capita -1 day -1 (Hardinsyah and Amalia, 2007). This is affirmed by Pradeksa et al (2014) in their research that the volume of wheat imports in Indonesia had increases year by year. Based on the trend calculation, the results have shown that there will be an additional import Copyright © 2019 Universitas Sebelas Maret volume of approximately 11,793 tons every year.…”
Section: Introductionmentioning
confidence: 89%
“…From 1996 to 1999, it had declined to 15.4 grams capita -1 day -1 , but increased again from 1999 to 2002 to 21.7 grams capita -1 day -1 and continued to increase until 2005 to 27.3 grams capita -1 day -1 (Hardinsyah and Amalia, 2007). This is affirmed by Pradeksa et al (2014) in their research that the volume of wheat imports in Indonesia had increases year by year. Based on the trend calculation, the results have shown that there will be an additional import Copyright © 2019 Universitas Sebelas Maret volume of approximately 11,793 tons every year.…”
Section: Introductionmentioning
confidence: 89%
“…For wheat, Indonesia faces increasing demand while having the little significant capability to grow the crop nationally [70]. This problem is caused by the lack of knowledge about wheat farming, low yield, incompatibility of wheat in low-land farming, and the susceptibility of wheat towards drought [71].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Each country has different natural resources so it will produce different goods. However, because people's needs are very diverse and the state can't meet all the needs of its people, this causes international trade to meet the needs within a country (Pradeksa et al, 2016).…”
Section: Theoritical Reviewmentioning
confidence: 99%